(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Cardiovascular diseases remain the main cause of death and disability in patients with type 2 diabetes mellitus (DM2) DM2 aggravates the underlying mechanisms of atherosclerosis and heart failure.